The Effectiveness of Organizational Design in Improving Performance at the Emergency Department of Luwuk Banggai Regional General Hospital - Anggun Puspita; Rinawati (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study aims to analyze the effectiveness of organizational design and its impact on the performance of the Emergency Department at Luwuk Banggai Regional General Hospital. A quantitative descriptive-analytic method was used, involving all 75 health and non-health workers in the ED selected through total sampling. Data were collected using a Likert-scale questionnaire and analyzed using Pearson correlation and simple linear regression tests. The findings indicated that the effectiveness of organizational design and ED performance were both in the high category, with means of 4.12 and 4.18 respectively. The correlation test showed a positive and significant relationship between organizational design effectiveness and ED performance (r = 0.713, p = 0.000). Regression analysis revealed that organizational design contributed 50.8 percent to ED performance (R² = 0.508). In conclusion, effective implementation of organizational design through clear structure, task distribution, communication, and interprofessional coordination leads to higher performance in the emergency department. The study emphasizes the importance of adaptive and collaborative organizational design in enhancing hospital service performance.